Sasak Boda Observed: The Preservation of Tebango Buddhists’ Cultural Heritage on Lombok Island, Indonesia - Muchammadun, Muchammadun; Amrulloh, Zaenudin; Aditya, Rahadiyand (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2023)
Although the government issued an accommodative policy protecting and supporting minority communities, statistics has shown a decline in the number of Buddhism followers in modern-day Lombok, Indonesia. This ethnographic study aims to reconsider the existence of a cultural heritage that provides sustainable values to community development. This study seeks to understand how the vernacular Buddhism of Sasak Boda in Tebango manages to strive as the minority and live their belief amid the dominating Sasak Muslim community. Data was collected through literature review, interviews, and observation. Findings indicate that the decline of Boda devotees in Dusun Tebango of Lombok in number has been affected by the public perception of the vernacular Buddhism movement. Despite such a reality becoming an anomaly in the discourses related to cultural heritage preservation, the Tebango Buddhists are capable of maintaining the tradition through customs that are tangible and intangible. This case signifies a premise that quantitative measurement alone is insufficient to study the sustainability of a local belief system such as the Sasak Boda. Consequently, this study argues that the state of maintainability and materiality of any culture act as determinant factors in the empowerment of locality-based communities.